C-reactive protein point-of-care testing in acutely ill children: a mixed methods study in primary care. Issue 4 (12th January 2016) - Van den Bruel, Ann; Jones, Caroline; Thompson, Matthew; Mant, David
Abstract : Background: Point-of-care C-reactive protein (CRP) testing of adults with acute respiratory infection in primary care reduces antibiotic prescribing by 22%. The acceptability and impact of CRP testing in children is unknown Objective: To determine the acceptability and impact of CRP testing in acutely ill children. Design: Mixed methods study comprising an observational cohort with a nested randomised controlled trial and embedded qualitative study. Subjects and setting: Children presenting with an acute illness to general practice out-of-hours services; children with a temperature ≥38°C were randomised in the nested trial; parents and clinical staff were invited to the qualitative study. Main outcomes: Informed consent rates; parental and staff views on testing. Results: Consent to involvement in the study was obtained for 200/297 children (67.3%, 95% CI 61.7% to 72.6%); the finger-prick test might have been a contributory factor for 63 of the 97 children declining participation but it was cited as a definite factor in only 10 cases. None of the parents or staff raised concerns about the acceptability of testing, describing the pain caused as minor and transient. General practitioner views on the utility of the CRP test were inconsistent. Conclusions: CRP point-of-care testing in children is feasible in primary care and is likely to be acceptable. However, it will not reduce antibiotic prescribing and hospital referrals until general practitioners accept its diagnostic value in children. Trial registration number: ISRCTN 69736109.